Cultivating Desmodesmus armatus (Chod.) Hegew. in recirculating aquaculture systems (RAS) waste water - Чебан, Лариса (My University, 2015)
The possibility of using RAS waste water as a cultivation medium for Desmodesmus armatus (Chod.) Hegew. was investigated. Algal biomass increased continuously reaching its maximum on the day 40 of cultivation. D. armatus culture was characterized by a maximum content of total proteins of 23% on day 40 of cultivation. At the same time, 17 proteinogenic amino acids, including 9 replaceable and 8 essential acids, were detected and identified in D. armatus biomass. Among these amino acids, maximum contents of asparagine and glutamine were noted. A gradual increase in the number of total photosynthetic pigments until day 40 of cultivation was also observed. On day 40, the content of chlorophyll a, b, and carotenoids in D. armatus cells was maximal at 11.17, 7.07, and 12.05 mg g-1 dry weight, respectively. Therefore, cultivating microalgae D. armatus in RAS waste water permits obtaining an active growing culture that is characterized by a constant increase of biomass and high nutrient contents.
Keywords: biomass; chlorophyll a, b; carotenoids; recirculating water system